A comparative study of clonidine and magnesium sulfate premedication on perioperative hormonal stress responses, hemodynamic stability and postoperative analgesia in patients with gallbladder diseases undergoing laparoscopic cholecystectomy. A randomized, double-blind, controlled study. Issue 1 (31st December 2022) - Mohamed Ali, Hatem Saber; Gad, Gad Sayed; Fayed, Hanan Mahmoud
ABSTRACT: Background: Hemodynamic derangement due to pneumoperitoneum and postoperative pain after laparoscopic cholecystectomy can be detrimental; this study investigated whether preoperative intravenous (I.V.) infusion of clonidine or Magnesium Sulfate (MgSO4 ) could attenuate hemodynamic responses, reduce serum cortisol level and improve post-operative analgesia. Materials and Methods: In total, 105 patients scheduled for laparoscopic cholecystectomy were randomized to either group C (I.V. infusion of clonidine 1.5 µg/kg), group M (I.V.infusion of MgSO2 30 mg/kg) or group S (I.V. infusion of isotonic saline) 15 min before induction of general anesthesia. Outcome variables were heart rate (H.R.), mean arterial pressure (MAP), serum cortisol leveln, total analgesic requirements and recovery time. Results: HR was significantly lower in group C than that in groups M and S. MAP and serum cortisol were significantly lower in groups C and M than that in control group. Pain score was better in groups C and M than group S at the first 2 hours post-operative with ( P values 0.024 and 0.19), respectively. Reduced post-operative analgesic requirement with delayed onset to first analgesic request were observed in groups C and M compared with the control group . Recovery time was significantly rapid in group C than that of groups M and S. Conclusion: Pre-operative I.V. infusion of clonidine and MgSO4 significantly attenuated the hemodynamic response to pneumoperitoneum, reduced serum cortisol level, reduced postoperative pain and analgesic requirement as compared to controls in patients undergoing laparoscopic cholecystectomy. Clonidine was superior compared to MgSO4 regarding H.R. control and rapid recovery.